PERTUMBUHAN TANAMAN DAN STRUKTUR ANATOMI DAUN KEDELAI, KACANG PANJANG, DAN KACANG TANAH PADA KETINGGIAN TEMPAT YANG BERBEDA - Andre, Andre; Harso, Wahyu; Rasyiid, Mustafid; Paserang, Asri Pirade; Iqbal, Moh; Sari, Retno (Biology Department, Mathematics and natural science, Tadulako University, 2025)
Soybeans, yardlong beans and peanuts are cultivated crops widely grown in the tropics at different altitudes. Differences in environmental factors between lowlands and highlands will affect plant growth and leaf anatomical structure. The study aimed to determine the growth and anatomical structure of the leaves of soybean, yardlong bean and peanut plants at different altitudes. The test plants were grown at two different altitudes. At an altitude of ± 20 masl, the test plants were placed in the greenhouse of the Biology Department of the Faculty of Mathematics and Natural Sciences, Tadulako University and at an altitude of ± 630 masl, the test plants were placed in Bahagia Village, Palolo District, Sigi Regency. The results showed that yardlong bean and peanut plants grown at an altitude of ± 630 masl had a lower stomatal density than those grown at ± 20 masl so the plant dry weight produced was also lower. Soybean plants have a larger stem diameter and plant dry weight at an altitude of ± 630 masl, these are due to the higher stomatal density and leaf thickness compared to those grown at an altitude of ± 20 masl.